2004
DOI: 10.1097/01.ju.0000108420.89313.0f
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Fraction Excretion Rate in Nocturnal Enuresis Correlates With Nocturnal Polyuria and Osmolality

Abstract: Purpose: We verify the sodium fraction excretion rate (FE Na) and potassium fraction excretion (FE K) rates in monosymptomatic nocturnal enuresis. We also correlate FE Na and FE K to urinary osmolality, nocturnal polyuria and vasopressin in the same population.Materials and Methods: A total of 438 children 6 to 15 years old (mean age 9.7) presenting with monosymptomatic nocturnal enuresis were recruited from different centers. Inclusion criteria were 3 or greater wet nights a week, no daytime incontinence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…In recent studies, investigators observed increased nocturnal fractional sodium excretion in enuretic patients with polyuria, suggesting that sodium excretion is correlated with nocturnal polyuria and nocturnal enuresis [2224]. In our study, we observed higher serum sodium concentrations in enuretic patients that had a lower day-to-night difference with respect to mean BP values.…”
Section: Discussionsupporting
confidence: 72%
“…In recent studies, investigators observed increased nocturnal fractional sodium excretion in enuretic patients with polyuria, suggesting that sodium excretion is correlated with nocturnal polyuria and nocturnal enuresis [2224]. In our study, we observed higher serum sodium concentrations in enuretic patients that had a lower day-to-night difference with respect to mean BP values.…”
Section: Discussionsupporting
confidence: 72%
“…However, during recent years, factors outside of this axis have also been implicated. Abnormal renal sodium handling (1,32), aberrations in the urinary osmotic excretion (29), and excess renal prostaglandin production (23) have all been associated with the nocturnal polyuria of enuresis. A recent study in enuresis has even indicated differences in blood pressure profiles during nights with excess diuresis (27).…”
Section: Discussionmentioning
confidence: 99%
“…In approximately two-thirds of monosymptomatic PNE patients, the circadian rhythm of arginine vasopressin (AVP) is underdeveloped, causing excessive nighttime urine production [14,15]. In around one-third of patients, the bladder is unstable and contracts during sleep [16].…”
Section: Introductionmentioning
confidence: 99%